Kapabilitas Pemerintah Desa dan BUMDes dalam Pengelolaan Wisata Umbul di Desa Ponggok Kabupaten Klaten - Ikhsan Muhammad Fajar; Zalzabila Puteri Herdini; Maulika Rahmatulaili; Shahla Eliza Nurhidayah; Dian Fitriani Afifah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This research explores the institutional capabilities of Local Government and BUMDes Tirta Mandiri in managing the tourism potential of Umbul in Ponggok Village, Klaten Regency. It aims to assess the extent to which local actors demonstrate capacity in the dimensions of thinking ahead, thinking again, and thinking across, as conceptualized within the dynamic governance framework. Employing a qualitative descriptive approach, this research adopts a case study method through field observations, in-depth interviews, and analysis of village planning documents. The findings indicate that the success of Umbul Ponggok’s tourism development is not merely attributable to its natural endowments, but also to the capacity of the village government and BUMDes to formulate long-term policy directions, critically review and refine existing initiatives, and foster cross-sectoral collaboration. These results highlight the critical importance of strengthening village institutional capabilities and human resources as a foundation for implementing adaptive and forward-looking policies.